Bread. (London : A Mushroom Book.)
Grains usually sown during the first days of the month of October, in fields which have already been ploughed. At this time the soil is warm enough to make the seeds swell and split open.
Keywords: Grains--Juvenile literature; Bread--Juvenile literature